Convergence of the Cyclic Reduction Algorithm for a Class of Weakly Overdamped Quadratics (Journal of Computational Mathematics, 2018)
In this paper, we establish a convergence result of the cyclic reduction (CR) algorithm for a class of weakly overdamped quadratic matrix polynomials without assumption that the partial multiplicities of the $n$th largest eigenvalue are all equal to 2. Our result can be regarded as a complement of that by Guo, Higham and Tisseur [SIAM J. Matrix Anal. Appl., 30 (2009), pp. 1593-1613]. The numerical example indicates that the convergence behavior of the CR algorithm is largely dictated by our theory.
Keywords: Weakly overdamped quadratics; Cyclic reduction; Doubling algorithm.